Parricide, Mental Illness, and Parental Proximity: The Gendered Contexts of Parricide in England and Wales - Miles, Caroline (Violence against women, 2023)
Parricide is underresearched in the UK, and the contexts of this gendered form of violence are poorly understood. Heide’s typology provides an advanced understanding of parricide in the United States, where the majority of parent-killings involve firearms. This article develops a UK-based analysis of the contexts of parricide, combining national statistics with police case study data (n = 57) and case review data (n = 21). Our findings indicate that mental illness plays a key role, combined with a gendered context of “parental proximity” and the simultaneous responsibilization and marginalization of parent-victims (particularly mothers), supporting the need for feminist analyses of parricide.